Optimal Low-Density Lipoprotein Cholesterol Levels in Adults Without Diabetes Mellitus: A Nationwide Population-Based Study Including More Than 4 Million Individuals From South Korea - Huh, Ji Hye; Park, Sang Wook; Go, Tae-Hwa; Kang, Dae Ryong; Lee, Sang-Hak; Kim, Jang-Young (Frontiers in Cardiovascular Medicine, 2022)
Background: Although the strong association between low-density lipoprotein cholesterol (LDL-C) and cardiovascular disease (CVD) is well-known, the threshold LDL-C level at which the risk of CVD begins to increase in individuals without diabetes mellitus (DM) remains unknown. We aimed to evaluate the association between incident CVD and serum LDL-C levels with or without statin use in individuals without DM. Methods: We identified 4,182,117 individuals without previous CVD who underwent a health screening examination in 2009 and 2011 from the Korean National Health Insurance Cohort database. The primary endpoint was a composite of cardiovascular deaths, myocardial infarction (MI) cases, and ischemic stroke cases. Results: During the median follow-up of 6 years, there were 51,961 CVD events that included 17,392 MI cases, 33,779 ischemic stroke cases, and 2,039 cardiovascular deaths. The LDL-C levels that were associated with an increased risk of CVD were ≥100 mg/dL in non-statin users and ≥130 mg/dL in statin users. However, even in individuals with lower LDL-C levels, all those with fasting plasma glucose (FPG) levels ≥110 mg/dL had a significantly higher risk of CVD. Conclusions: We demonstrated that LDL-C levels ≥100 mg/dL were correlated with an increased risk of CVD in individuals without DM and a history of CVD. We found that a glucose, cholesterol interaction increased CVD risk, and modestly elevated FPG levels (110–125 mg/dL) were associated with a higher CVD risk even in individuals with well-controlled LDL-C levels.